2022
DOI: 10.7759/cureus.30539
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity and Cardiovascular Risk Factors Among Type 2 Diabetes Mellitus Patients in Al-Khobar, Saudi Arabia

Abstract: Background: The prevalence of obesity has grown significantly worldwide. It is considered a major cardiovascular risk factor among type II diabetes mellitus (T2DM) patients.Objectives: The main objective of this study is to determine the prevalence of obesity in patients with T2DM at King Fahd University Hospital (KFUH), Al-Khobar, and to assess the relationship between T2DM and cardiovascular risk factors with body mass index (BMI) and waist to hip ratio (WHR).Methods: A retrospective, cross-sectional study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…The hip circumference was measured at the largest standing horizontal circumference of the buttocks, and the waist circumference was measured at the lowest standing horizontal circumference between the lower margin of the rib cage and the iliac crest. The waist-to-hip ratio (WHR) was also determined by dividing hip circumference by waist circumference, which is the ratio of waist circumference to hip circumference in cm (3). Well-trained nutritionists measured these variables.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The hip circumference was measured at the largest standing horizontal circumference of the buttocks, and the waist circumference was measured at the lowest standing horizontal circumference between the lower margin of the rib cage and the iliac crest. The waist-to-hip ratio (WHR) was also determined by dividing hip circumference by waist circumference, which is the ratio of waist circumference to hip circumference in cm (3). Well-trained nutritionists measured these variables.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of T2DM has been steadily increasing worldwide, and it is a major public health concern due to its association with various comorbidities, including cardiovascular disease (CVD) and chronic kidney disease (CKD) (2). In addition to the traditional risk factors, recent studies have suggested that adipose tissue-derived hormones such as Leptin play a crucial role in the pathogenesis of T2DM and its related complications (3, 4).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations